Neuro-endoscopic management of hemorrhagic moyamoya disease in the acute stage: single institute experience. (2nd December 2019) - Mino, Masaki; Fujimura, Miki; Endo, Hidenori; Endo, Toshiki; Sato, Kenichi; Tominaga, Teiji
ABSTRACT: Background : Management of hemorrhagic moyamoya disease (MMD) is one of the most challenging issues in neurosurgical practice. Recently, surgical revascularization by superficial temporal artery-middle cerebral artery anastomosis was reported to significantly reduce the risk of re-bleeding in hemorrhagic-onset MMD patients in the chronic state, but the optimal treatment strategy in the acute phase of hemorrhagic MMD is undetermined. Thus, we retrospectively analyzed our surgical results for hemorrhagic MMD in the acute stage, focusing on the efficacy of neuro-endoscopic management for hematoma removal. Materials and methods : Among 26 consecutive hemorrhagic MMD patients who were managed at our institution in the acute stage, 8 patients with intracerebral hemorrhage underwent surgical evacuation of the hematoma. All patients were diagnosed with MMD before surgery by magnetic resonance angiography and/or catheter angiography. Results : The initial surgical procedure was neuro-endoscopic hematoma removal in seven patients and microsurgical hematoma removal by craniotomy in one patient. One patient treated by the neuro-endoscopic procedure required subsequent small craniotomy due to difficulty in hemostasis. Satisfactory hematoma evacuation was achieved in all eight patients, as demonstrated by post-operative computed tomography, although one patient who was deeply comatose before surgery died in the early post-operative period. Conclusion : Neuro-endoscopic hematoma removal may be the optimal management method for hemorrhagic MMD in the acute stage in terms of the maximum preservation of pre-existing collateral anastomosis without affecting the potential donor vessels used for future revascularization surgery. Abbreviations: MMD: Moyamoya disease; STA: Superficial temporal artery; MCA: Middle cerebral artery; JAM: Japan Adult Moyamoya; ICH: Intracerebral hemorrhage; IVH: Intraventricular hemorrhage; SAH: Subarachnoid hemorrhage; CT: Computed tomography; TE: Total evacuation; PE: Partial evacuation; SMR: Light mass reduction; MR: Magnetic resonance; mRS: Modified Rankin scale; GCS: Glasgow Coma Scale; ICP: Intracranial pressure.